ENHANCING MATERNAL SELF-EFFICACY IN COMPLEMENTARY FEEDING THROUGH HEALTH EDUCATION: A QUASI-EXPERIMENTAL STUDY - Fitriana Noor Khayati; Setianingsih Setianingsih; Chori Elsera; Dita Tri Wahyuningsih (Jurnal SMART Keperawatan, 2025)
Providing good nutrition aims to reduce stunting rates. Giving complementary foods is also influenced by the mother's self-efficacy. It is hoped that education for mothers can increase their self-efficacy in providing complementary foods. This research aimed to determine the effect of education on maternal self-efficacy in providing complementary foods to children aged 6-24 months. The method used was Quasi-experimental with one group pretest-posttest design. It was conducted in Jiwan Village, Karangnongko District, Klaten Regency. The population is mothers who have children under five in Jiwan Village with a total of 224 people. The sampling technique used was purposive sampling with a sample size of 29 mothers. The intervention was education, using brainstorming and lecture methods and audiovisual media and booklets. The analysis used is the Wilcoxon test with a confidence level of 95%. The average self-efficacy score before education was 55.86 ± 5.36 and the score after education was 58.79 ± 7.03 an increase in the average mother's self-efficacy score in providing complementary foods. The results show that the Z count is -3.109 and the sig is 0.002. This shows that it is less than 0.05 (5% error rate), so it can be concluded that there is a difference in self-efficacy results before and after education on giving complementary foods. It is hoped that the education program for providing complementary foods will be implemented sustainably with the development of educational media.